Beaded of Goldschmidt, an antimorphic allele of Serrate, encodes a protein lacking transmembrane and intracellular domains. - Hukriede, N.A.; Fleming, R.J. (Genetics, 1997)
Serrate (Ser) is an essential gene in Drosophila melanogaster best known for the Ser dominant (SerD) allele and its effects on wing development. Animals heterozygous or homozygous for SerD are viable and exhibit loss of wing margin tissue and associated bristles and hairs. The Beaded of Goldschmidt (BdG) allele of Ser, when heterozygous to wild type, will also produce animals exhibiting loss of wing margin material. However, animals homozygous for BdG exhibit a larval lethal phenotype comparable to animals homozygous for loss-of-function Ser alleles. BdG is a partial duplication of the Ser locus with a single 5' Ser-homologous region and two distinct 3' regions. Meiotic recombination between BdG and a wild-type Ser chromosome demonstrated that only one DNA lesion, caused by the insertion of a transposable roo element into the coding regions of the Ser transcript, appears capable of generating BdG phenotypes. Due to the roo insertion, the protein product is predicted to be prematurely truncated and lack an extracellular cysteine-rich region along with the transmembrane and intracellular domains found within the normal SERRATE (SER) protein. The loss of these protein domains apparently contributes to the antimorphic nature of this mutation.